2015
DOI: 10.1177/0142723715584227
|View full text |Cite
|
Sign up to set email alerts
|

Narrative coherence of Mandarin-speaking children with high-functioning autism spectrum disorder: An investigation into causal relations

Abstract: Previous research has shown that individuals with autism spectrum disorder (ASD) had difficulty integrating narrative information coherently. The majority of these studies focused on people narrating in English; however, little is known about the narrative abilities of Mandarin-speaking individuals with ASD. This study investigates the ability of Mandarin-speaking children with ASD to achieve narrative coherence. The data consist of narratives from 18 children with high-functioning ASD (M age : 8.23) and 18 ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
0
21
1
1
Order By: Relevance
“…Given the fact that narrative production has important academic and social implications, it raised the question of how narrative skills may be supported for children with ASD, specifically can narrative performance be improved by reducing the task demand and providing more structure within the story, such as a script-framework. Although more recently research has begun to examine the link between language abilities and narrative competence by rigorously matching children with ASD to their NT peers (e.g., Diehl et al, 2006), few studies have examined how variability in language levels may contribute to differences in narrative performance among children with ASD (Norbury et al, 2014;Sah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that narrative production has important academic and social implications, it raised the question of how narrative skills may be supported for children with ASD, specifically can narrative performance be improved by reducing the task demand and providing more structure within the story, such as a script-framework. Although more recently research has begun to examine the link between language abilities and narrative competence by rigorously matching children with ASD to their NT peers (e.g., Diehl et al, 2006), few studies have examined how variability in language levels may contribute to differences in narrative performance among children with ASD (Norbury et al, 2014;Sah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has found that children and adults with ASD have a difficult time organizing plot structure and causally linking story events in a meaningful way that relays the overall 'gist', resulting in narratives that are less coherent than their NT peers (Barnes & Baron-Cohen, 2012;Diehl et al, 2006;King et al, 2014;Losh & Capps, 2003;Manolitsi & Botting, 2011;Sah & Torng, 2015;Suh et al, 2014). Additionally, studies have illustrated that appropriately utilizing linguistic devices that create a more cohesive, or locally connected, story is often a challenge for both children and adults with ASD.…”
Section: Narrative Impairments In Children With Asdmentioning
confidence: 99%
“…For the purposes of this essay, the semantics of the story and the ways by which it is conveyed in the narratives will be referred to as "semantic-pragmatic" aspects of the narrative. For example, children with ASD were found to relate to causal aspects of the story less often than their TD peers (Losh and Capps, 2003;Sah and Torng, 2015). Children with ASD were also found to include fewer main story components and to make fewer references to internal states and their causes as compared with their TD controls (Makinen et al, 2014).…”
Section: Narrative Skills In Asdmentioning
confidence: 99%
“…Despite some similarities in language abilities [25,37,38], various studies reported a wide variety of linguistic differences and impairments for children with ASD [39][40][41], particularly in the discursive and pragmatic aspects, in which various kinds of rules and processes govern the contextual suitability of language [42][43][44][45][46]. Some literature on referential choices made by children with ASD proposed that, due to impairments in attention, working memory, mental processes and difficulties in using pronouns, they tended to adhere their narratives to the explicit referential expressions such as full lexical noun phrases [18,47].…”
Section: Persian Referential Expressionsmentioning
confidence: 99%